2015
DOI: 10.1074/jbc.m114.620500
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Equine Lactadherin-derived Peptides That Inhibit Rotavirus Infection via Integrin Receptor Competition

Abstract: Background: Human milk lactadherin protects breastfed infants against symptomatic rotavirus infections. Results: A 20-aa peptide (namely pDGE-RGD) derived from equine lactahderin inhibits human rotavirus infectivity. Conclusion: pDGE-RGD interacts specifically with ␣2␤1 integrin, thus hindering the rotavirus-cell attachment process. Significance: The discovery of the pDGE-RGD peptide may prove useful in the development of inhibitors of receptor recognition by rotavirus or other integrin-using viruses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 57 publications
1
18
0
Order By: Relevance
“…African green monkey kidney cells (Vero cells; ATCC CCL-81) were grown as monolayers in Eagle's minimal essential medium (Gibco/BRL) supplemented with 10% fetal bovine serum and 1% antibiotic-antimycotic solution. The HRoV strains Wa (ATCC VR-2018), HRV408 (ATCC VR-2273), and HRV248 (ATCC VR-2274) and the BRoV strain NCDV (ATCC VR-1290) were activated with 5 µg/mL porcine pancreatic trypsin type IX (Sigma-Aldrich Co.) for 30 min at 37°C and propagated in MA104 cells using DMEM containing 0.5 µg of trypsin per mL as described previously (Civra et al, 2015). Viral titers are expressed as focus-forming units (FFU) per milliliter.…”
Section: Cell Lines and Virusesmentioning
confidence: 99%
See 1 more Smart Citation
“…African green monkey kidney cells (Vero cells; ATCC CCL-81) were grown as monolayers in Eagle's minimal essential medium (Gibco/BRL) supplemented with 10% fetal bovine serum and 1% antibiotic-antimycotic solution. The HRoV strains Wa (ATCC VR-2018), HRV408 (ATCC VR-2273), and HRV248 (ATCC VR-2274) and the BRoV strain NCDV (ATCC VR-1290) were activated with 5 µg/mL porcine pancreatic trypsin type IX (Sigma-Aldrich Co.) for 30 min at 37°C and propagated in MA104 cells using DMEM containing 0.5 µg of trypsin per mL as described previously (Civra et al, 2015). Viral titers are expressed as focus-forming units (FFU) per milliliter.…”
Section: Cell Lines and Virusesmentioning
confidence: 99%
“…Rotavirus-cell binding assays were performed as described previously (Civra et al, 2015). Trypsin-activated RoV strains Wa, HRV248, HRV408, and NCDV were treated as described for the neutralization assays.…”
Section: Rotavirus-cell Binding Assaymentioning
confidence: 99%
“…It has been reported that bioactive peptides from proteins in foods have several functions [2][3][4][5][6][7][8]. Milk casein yields many peptides through hydrolysis with digestive and other enzymes.…”
Section: The Search For Peptides Derived From Casein With Anti-allergmentioning
confidence: 99%
“…It has been reported that polyphenolic compounds, such as epigallocatechin gallate, show anti-allergic effects, but there have been few reports regarding the anti-allergenic effect of peptides. It has been reported that bioactive peptides from proteins in foods have several functions, such as reduction in blood pressure [2][3][4], activation of immune cells [5,6], antiviral actions [7], and improvement of lipid metabolism [8]. Milk casein yields many peptides through hydrolysis with digestive and other enzymes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation